Kesalahan Berbahasa pada Bahasa Melayu di Thailand dan Solusinya dalam Perspektif Hasil Studi di Indonesia - Sulaiman Saha; Rusdhianti Wuryaningrum (Nuances of Indonesian Language, 2022)
This study is conducted to answer Language errors in Malay and their solutions. This study deals with difficulties coped by the teachers in planning, conducting and evaluating the learning.  Methods of  collection data  using the interview method. The technique of data analysis is done by using reduction, presentation, conclusion drawing and data verification. The amount research respondents are around 8 people, namely the teachers at Tadika Al-Hidayah Bendang Jerambung, Southern Thailand. Based on the results of the study, it shows that there are still language errors in Malay, such as the use of the word contamination of the Patani area in Malay, the illogical use of sentences, the use of inappropriate punctuation marks, and errors in the use of prepositions. The factors that cause language errors in Malay are the lack of literacy activities, the habit of using everyday language, the lack of seriousness in learning time in class, and the Malay language learning curriculum cannot fulfill. Based on the perspective of learning in Indonesia, the solutions that can be offered are the implementation of the School Literacy Movement, the preparation of good learning plans, and the application of text-based learning.